Retrieving Information using Reversible Data Hiding (International Journal of Scientific Research and Management (IJSRM), 2014)
: Nowadays huge attention is paid to Reversible Data Hiding (RDH) in encrypted images, since it maintains the excellent property that the original cover can be losslessly recovered after embedded data is extracted while protecting the image content’s confidentiality. Recent Methods such as reserving room before encryption with a traditional RDH algorithm sometimes results in error and complicated usage at the time of data extraction and/or image restoration .Hence to overcome this problem, this project propose an efficient method which uses by combining cryptographic primitives based encryption with Histogram Shifting-based RDH algorithm, a high capacity and low distortion can be achieved efficiently, and thus it is easy for the data hider to reversibly embed data in the encrypted image. The proposed method can achieve real multi level reversibilit y, that is, data extraction and image recovery are free of any error. Experiments show that this method can embed more than 10 times as large payloads for the same image quality.